2013 Benjamin Franklin Medal in Mechanical Engineering presented to Subra Suresh. Issue 7 (July 2015) - Todd, Judith A.; Copley, Stephen M.
Abstract The mechanical behavior of materials can be modeled and evaluated across multiple scales that encompass: atomic and molecular rearrangements to create incipient defect nuclei; combination or growth of such nuclei to form micro-scale and subsequently macro-scale defects; and finally development of critical flaw sizes that result in final failure of engineering structures. Through an understanding of the mechanisms governing these processes, which depend on the loading conditions and the specific materials, new or modified materials systems designs can be integrated with advanced structural concepts to advance our energy, civil, transportation and healthcare infrastructures, among others. Subra Suresh׳s research includes development of novel experimental techniques and the discovery of new mechanistic processes that are broadly applicable to essentially every major class of natural and synthetic materials, including metals, ceramics, polymers, composites, biomolecules and biological cells. Beginning in the 1970s, he elucidated mechanisms of near-threshold fatigue crack growth in steels and aluminum alloys, contributing to improved alloy design for nuclear pressure vessels, fossil plants, offshore structures and aircraft. Subsequent work identified mechanisms for toughening brittle ceramics against fatigue crack growth under cyclic compressive loads. Turning to the microscale and the study of thin films, he developed new methods for extracting elastoplastic and functional properties of materials from small-volume contact probing. This led to new theories, computation and experiments on material and surface design through controlled gradients in composition and properties, and applications to coatings. At the nanoscale, he experimentally discovered nanocrystallization of bulk amorphous alloys during nanoindentation, and also showed how nanoscale twins could optimize the strength and ductility of fine grained metals. Most recently, he is noted for demonstrating the effects of disease-induced changes to human red blood cell deformability and biorheology, and for linking these changes to human diseases such as malaria.